“Don’t Be Your Selfie”: The Pedagogical Importance of the Otherness in the Construction of Teenagers’ Identity - Alonso-Sainz, Tania (Identity in a Hyperconnected Society: Risks and Educative Proposals, 2023)
This work aims to discover the pedagogical importance of otherness in the construction of the identity of teenagers. To do this, we will use the work of Charles Taylor on the construction of identity. Later, we ask ourselves how this otherness is constructed in societal networks, paying special attention to the activity of posting selfies. Recent research has looked for the relationship between narcissism and the use of social networks. We will conclude that social networks, far from diverting attention from the human, point to an ontological trait of the human being, which is precisely the need for otherness in the construction of our identity.
Keywords: identity; Instagram; selfies; Teenagers; Scopus(2)